METHODS OF EXAMINATION OF CHRONIC ETHMOIDITIS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
For the first time, the features of the anatomical structure of the ethmoid bone were determined in patients with ethmoiditis. The relationship between the anatomical structure of the ethmoid bone cells and the volume of the inflammatory process, its localization and severity has been determined. For the first time, the frequency of damage to different groups of cells was determined in isolated ethmoiditis and in combination with damage to other sinuses.